2019
DOI: 10.1371/journal.pone.0226578
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of metabolite detection in cystic fibrosis sputum reveals heme correlates with lung function decline

Abstract: The bacterial growth environment within cystic fibrosis (CF) sputum is complex, dynamic, and shaped by both host and microbial processes. Characterization of the chemical parameters within sputum that stimulate the in vivo growth of airway pathogens (e.g. Pseudomonas aeruginosa) and their associated virulence factors may lead to improved CF treatment strategies. Motivated by conflicting reports of the prevalence and abundance of P. aeruginosa-derived metabolites known as phenazines within CF airway secretions,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…For P. aeruginosa and S. aureus in particular, the current work suggests that heme utilization may prevent iron starvation by CP during infection and may consequently alter their dynamics during coinfection. A recent study indicated that heme levels in the CF lung negatively correlate with lung function ( 60 ). Thus, the possibility that heme enables resistance of S. aureus and P. aeruginosa to iron-sequestering host factors such as lactoferrin and CP in the CF lung, and ultimately contributes to loss of lung function, warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For P. aeruginosa and S. aureus in particular, the current work suggests that heme utilization may prevent iron starvation by CP during infection and may consequently alter their dynamics during coinfection. A recent study indicated that heme levels in the CF lung negatively correlate with lung function ( 60 ). Thus, the possibility that heme enables resistance of S. aureus and P. aeruginosa to iron-sequestering host factors such as lactoferrin and CP in the CF lung, and ultimately contributes to loss of lung function, warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…3D ), and we speculate that this is due to increased pyochelin production by ∆ pvdA cells, but future studies will be required to test this model. It was interesting to find that in WT/∆ lasR coculture, heme-related proteins, hasAP , hasS , and hasD , were among the top eight most-upregulated genes by the ∆ lasR strain because the presence of lasR mutants and heme content are both reported biomarkers of disease progression in CF patients ( 13 , 86 ). Coculture-induced lasR mutant phenotypes may link these two correlative observations.…”
Section: Discussionmentioning
confidence: 99%
“…injected PYO in BALB/c mice significantly increased glutathione-S-transferase activity only in the heart, but not in other tissues 53 . Although detection of PYO and of its metabolites is not an easy task 54 , our pharmacokinetic profiling was able to reliably detect PYO, and indicated that optimization of PYO administration in mice is required before testing its effect on behavioral parameters in vivo.…”
Section: Discussionmentioning
confidence: 95%